Punishment of Illegal Fishing Perpetrators in Indonesia in the Perspective of Equality before the Law - Marimin, Marimin; Setyawan, Lazarus Tri; Sularto, RB. (SASI, 2022)
Introduction: Equality before the law is one of the important principles in the enforcement of criminal law in Indonesia, so it is important to pay attention to it. The punishment of illegal fishing perpetrators in ZEEI is not on the principle of equality before the law. Although the Fisheries Law adopted the 1982 UNCLOS, UNCLOS itself did not state the prohibition on the application of confinement instead of fines. Therefore, the application of fines for illegal fishing in ZEEI does not conflict with the 1982 Fisheries Law and UNCLOS. The fines of imprisonment are also applied to foreign nationals to ensure that the fines paid will be paid.Purposes of the Research: This study aims to analyze and explain the concept of equality before the law in criminal law enforcement and whether the punishment of illegal fishing perpetrators in Indonesia is following the principle of equality before the law, especially related to the application of confinement instead of fines for Indonesian citizens and foreign nationals.Methods of the Research: This research belongs to the type of normative legal research with a legal and conceptual approach. The research material used is secondary data derived from primary, secondary, and tertiary legal materials. The research materials were collected using a literature study and then analyzed qualitatively and then conclusions were drawn using the deductive method.Results of the Research: Equality before the law is one of the important principles in the enforcement of criminal law in Indonesia, so it is important to pay attention to it. The punishment of illegal fishing perpetrators is not by the principle of equality before the law. Although the Fisheries Law adopted the 1982 UNCLOS, UNCLOS itself did not emphasize the prohibition on the application of confinement instead of fines. Therefore, the application of confinement in lieu of fines for perpetrators of illegal fishing in the ZEEI does not conflict with the 1982 Fisheries Law and UNCLOS. The penalty of confinement instead of an important fine is also applied to foreign nationals to ensure that the fines imposed will be paid.